Pengaruh Pengalaman, Profesionalisme, Kompleksitas Tugas, Kompetensi terhadap Kinerja Auditor (Studi pada Auditor BPK RI Perwakilan Provinsi Jambi) - Dewi, Ristika Pra; Zaky, Achmad (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study is to examine the influence of experience, professionalism, task complexity, and competence on performance of auditors. The dependent variable used in this study is performance of auditors, while independent variable used are experience, professionalism, task complexity, and competence. This study uses 38 respondens at Audit Board of Republic Indonesia  Representative Office of  Jambi  using  a  census  method.  Data analysis method used is multiple linear regression statistical analysis. Results of regression analysis show that the task complexity and competence influence performance of auditors, while experience and professionalism have no effect on the performance of auditors. The most dominant variable in influencing the performance of auditors is the task complexity.Keywords: Experience, professionalism, task complexity, competence, performance of auditors.